99mTc-MIBI SPECT in primary hyperparathyroidism - Schmidt, M.; Thoma, N.; Dietlein, M.; Moka, D.; Eschner, W.; Faust, M.; Schröder, W.; von Hülst-Schlabrendorff, M.; Ehses, W.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2008)
Aim of the study was to analyse the influence of a concomitant vitamin D deficiency on the results of 99mTc-MIBI studies in patients (pts) with primary hyperparathyroidism (pHPT). Patients, methods: Between January 1998 and May 2004, 71 pts with pHPT had undergone operation after a 99mTc-MIBI study of whom 54 pts (76%) had normal values of 25-OH-vitamin D3 and 17 pts (24%) had vitamin D deficiency. Results of a dual-phase 99mTc-MIBI protocol with SPECT were compared with histopathology. Results: In 54 pts with normal vitamin D values late SPECT images identified more lesions (n = 51, sensitivity 91%) than early planar (n = 45, sensitivity 82%) or late planar images (n = 50, sensitivity 88%). In 17 pts with vitamin D deficiency late SPECT images identified more lesions (n = 13, sensitivity 72%) than early planar (n = 10, sensitivity 56%) or late planar images (n = 10, sensitivity 56%) too. In pts with vitamin D deficiency the sensitivity of a 99mTc-MIBI SPECT study was lower than in those with normal vitamin D status (72% vs. 91%) and dependent on the value for PTH. However, the results did not reach statistical significance: early planar: p = 0.1625; late planar: p = 0.0039; 99mTc-MIBI SPECT: p = 0.1180. Conclusion: The likelihood of a pathological 99mTc-MIBI study being obtained in pts with pHPT is dependent on the parathyroid hormone level. However, a negative influence of a low vitamin D level on the scintigraphic detection rate of a parathyroid adenoma could not be proven which may be due to the low number of pts with vitamin D deficiency.
Keywords: Primary hyperparathyroidism; parathyroid hormone; 25-OH-vitamin D deficiency; 99mTc-MIBI scintigraphy; planar and SPECT imaging; single-tracer dual-phase protocol